Ethnobotanical assessment of medicinal plants used by indigenous tribes in Mainpat Hills, Chhattisgarh: Quantitative indices and therapeutic potential - Kerketta, Rakesh; Nanda, Monali; Shahi, Mamta Patra; Shahi, Sushil Kumar (Ethnobotany Research and Applications, 2026)
Background: This study explores traditional medicinal knowledge among indigenous tribes of Mainpat hills, Chhattisgarh, documenting their reliance on ethnomedicinal plants for treating common ailments. Using indices like UV, RFC, and FL, it identifies species with therapeutic potential, stressing the need to conserve both indigenous knowledge and biodiversity. The aim is to document and analyse traditional plant use and highlight species of high medicinal value. Methods: An ethnobotanical survey was conducted across tribal villages in Mainpat hills using door-to-door interviews with local inhabitants and healers. A total of 17 informants participated in the study, who are practicing healers. Data on plant names, parts used, preparation, treated ailments, and administration routes were collected via structured questionnaires. Quantitative indices (UV, ICF, RFC, FL, ROP) were applied for analysis. Results: A total of 46 medicinal plant species belonging to 33 families were documented for the treatment of 36 ailments distributed across 11 disease categories. Leaves were the most frequently used plant part (39%), predominantly prepared as oral decoctions. The results indicate a strong dependence of local communities on herbal medicine for primary healthcare. Vitex altissima L.f. showed the highest use value, indicating broad therapeutic application, while Vernonia amygdalina Delile showed the lowest. Respiratory ailments exhibited the highest consensus among informants. Species such as Punica granatum L., Citrus limon (L.) Osbeck, and Tinospora cordifolia (Willd.) Hook.f. & Thomson showed the highest therapeutic specificity and cultural importance within the community. Conclusion: The indigenous communities of Mainpat hills exhibit rich ethnomedicinal knowledge and dependence on plant-based remedies for healthcare. Key plants with high UV and FL indicate strong therapeutic and cultural value. The findings highlight the need for pharmacological validation and conservation of both traditional knowledge and biodiversity. Keywords: Ethnomedicine, medicinal plants, traditional medicinal system, tribal communities, Surguja